2015
DOI: 10.2147/ott.s93305
|View full text |Cite
|
Sign up to set email alerts
|

Dendrobium candidum inhibits MCF-7 cells proliferation by inducing cell cycle arrest at G2/M phase and regulating key biomarkers

Abstract: BackgroundBreast cancer is one of the most frequently occurring cancers in women. In recent years, Dendrobium candidum has played a part in antihyperthyroidism and anticancer drugs. This study aims to examine the antitumor effect of D. candidum on breast cancer.MethodsHuman breast cancer cell line MCF-7 and normal breast epithelial cell line MCF10A were used to observe the effects of D. candidum treatment on human breast cancer. 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…The several phenol derivatives detected in these extracts arrest the cell cycle and induce apoptosis through morphological changes like cell shrinkage, chromatin condensation, and nuclear fragmentation [ 28 , 55 , 56 ], thereby serving as an important defense mechanism preventing the proliferation of cancer cells. Like other studies of the anticancer activities of Dendrobium species [ 21 – 27 ], this study too, found that phenol derivatives induces the apoptosis of cancer cells. Phenol derivatives of extracts do exhibit both antioxidant and anticancer effects [ 2 4 , 57 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The several phenol derivatives detected in these extracts arrest the cell cycle and induce apoptosis through morphological changes like cell shrinkage, chromatin condensation, and nuclear fragmentation [ 28 , 55 , 56 ], thereby serving as an important defense mechanism preventing the proliferation of cancer cells. Like other studies of the anticancer activities of Dendrobium species [ 21 – 27 ], this study too, found that phenol derivatives induces the apoptosis of cancer cells. Phenol derivatives of extracts do exhibit both antioxidant and anticancer effects [ 2 4 , 57 ].…”
Section: Discussionsupporting
confidence: 76%
“…The natural antioxidant-rich compounds of D. moniliforme engage in many biological activities, including promoting the production of body fluids, serving neuroprotective, immunomodulatory and antioxidant functions [ 2 , 20 ]. D. candidum has previously been shown to have in vitro anticancer effects on human carcinoma cells [ 21 – 27 ]. Indeed, it is often the case that bioactive agents of folk medicine help prevent the development of cancer by inducing apoptosis [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is encouraging that natural products from medicinal plants have been shown to be valuable sources for the development of novel drugs against a range of diseases ( Niu et al, 2012 ; Sacco et al, 2013 ). One example is the orchid Dendrobium officinale ( Zhao et al, 2014 ), a traditional Chinese high-value medicinal herb that is widely used across Asia ( Zhao et al, 2014 ; Sun et al, 2016 ). This plant contains polysaccharides, stillnoids, alkaloids, amino acids, and trace elements and is known to exert a number of positive effects on human health ( Li et al, 2010 ; Li L. et al, 2011 ), including anti-tumor, anti-oxidative, anti-chronic inflammation, anti-obesity, anti-hypertensive, hypoglycemic, neuron protection, and immune system modulation activities ( Xiao et al, 2011 ; Zhao et al, 2014 ; Sun et al, 2016 ; Lee et al, 2017 ; Wang Q. et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [32] confirmed that depletion of eIF-3d reduces non-small cell lung cancer cell proliferation via enhancement of cell cycle arrest in the G2/M phase. Sun et al [33] proved that the dendrobium candium could suppress the proliferation of MCF-7 cells by increasing G2/M arrest. Here, we suggest that miR-219-5p suppressed ESCC cell proliferation and induced G2/M phase arrest by directly downregulating CCNA2 expression.…”
Section: Discussionmentioning
confidence: 99%